Polymorphism rs7079 in miR-31/-584 Binding Site in Angiotensinogen Gene Associates with Earlier Onset of Coronary Artery Disease in Central European Population - Novák, Jan; Maceková, Soňa; Héžová, Renata; Máchal, Jan; Zlámal, Filip; Hlinomaz, Ota; Rezek, Michal; Souček, Miroslav; Vašků, Anna; Slabý, Ondřej; Bienertová-Vašků, Julie (Genes, 2022)
Angiotensinogen (AGT) represents a key component of the renin-angiotensin-aldosterone system (RAAS). Polymorphisms in the 3' untranslated region (3'UTR) of the AGT gene may alter miRNA binding and cause disbalance in the RAAS. Within this study, we evaluated the possible association of AGT +11525C/A (rs7079) with the clinical characteristics of patients with coronary artery diseases (CAD). Selective coronarography was performed in 652 consecutive CAD patients. Clinical characteristics of the patients, together with peripheral blood samples for DNA isolation, were collected. The genotyping of rs7079 polymorphism was performed with TaqMan® SNP Genotyping Assays. We observed that patients with the CC genotype were referred for coronarography at a younger age compared to those with the AA+CA genotypes (CC vs. AA+CA: 59.1 ± 9.64 vs. 60.91 ± 9.5 (years), p = 0.045). Moreover, according to the logistic regression model, patients with the CC genotype presented more often with restenosis than those with the CA genotype (p = 0.0081). In conclusion, CC homozygotes for rs7079 present with CAD symptoms at a younger age compared with those with the AA+CA genotype, and they are more prone to present with restenosis compared with heterozygotes.
Keywords: rs7079; MicroRNAs; lidé; polymorfismus genetický; Angiotensinogen; 3' nepřekládaná oblast; nemoci koronárních tepen; Coronary Artery Disease; age; Polymorphism, Genetic; restenosis; vazebná místa; 3' Untranslated Regions; mikro RNA; angiotensinogen; coronary artery disease; Binding Sites; Humans